Ngaben Panca maha bhuta: Kepercayaan tradisi pemakaman Ngaben Hindu Bali - Zahra, Nazira Rashiqa; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
Ngaben is a unique and significant funeral ceremony in Hinduism, particularly in Bali. In addition to serving as a means of burying the deceased, Ngaben is also considered a medium to free the spirit of the departed from worldly bonds so it can achieve moksha, or liberation from the cycle of reincarnation (samsara). One of the key aspects associated with the Ngaben ceremony is the concept of Panca Maha Bhuta, which refers to the five fundamental elements of nature that, according to Hindu teachings, form the basis of the human body and the universe. This article will delve deeply into how the Panca Maha Bhuta is applied in the Ngaben tradition and how these five elements play a role in the process of liberating the spirit, spiritual transformation, and the connection between the body, soul, and the universe.